CFP Board financial planning competency handbook - Certified Financial Planner Board of Standards (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
The official CFP guide for career excellence CFP Board Financial Planning Competency Handbook is the essential reference for those at any stage of CFP certification and a one-stop resource for practitioners looking to better serve their clients. This fully updated second edition includes brand new content on connections diagrams, new case studies, and new instructional videos, and a completely new section devoted to the interdisciplinary nature of financial planning. You'll gain insights from diverse fields like psychology, behavioral finance, communication, and marriage and family therapy to help you better connect with and guide your clients, alongside the detailed financial knowledge you need to perform to the highest expectations as a financial planner. The only official CFP Board handbook on the market, this book contains over ninety chapters that are essential for practitioners, students, and faculty. Whether a practitioner, student, or faculty member, this guide is the invaluable reference you need at your fingertips. Comprehensive, clear, and detailed, this handbook forms the foundation of the smart financial planner's library. Each jurisdiction has its own laws and regulations surrounding financial planning, but the information in this book represents the core body of knowledge the profession demands no matter where you practice. CFP Board Financial Planning Competency Handbook guides you from student to practitioner and far beyond, with the information you need when you need it.
Professional Practice Capabilities -- In Practice -- Rebecca -- Mike -- Note -- Chapter 32 Types of Investment Risk -- Connections Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- Rosemary and James -- Chapter 33 Quantitative Investment Concepts -- Connections Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- Rodolfo and Henrietta -- Chapter 34 Measures of Investment Returns -- Connections Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- Robert and Mary -- Note -- Chapter 35 Asset Allocation and Portfolio Diversification -- Connections Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- Harry -- Missy -- Notes -- Chapter 36 Bond and Stock Valuation Concepts -- Connections Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- Georgette -- Tobe and Steve -- Notes -- Chapter 37 Portfolio Development and Analysis -- Connections Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- Robert and April -- Chapter 38 Investment Strategies -- Connections Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- George -- Kenneth -- Chapter 39 Alternative Investments -- Connections Diagram -- Introduction -- Learning Objective -- In Class -- Professional Practice Capabilities -- In Practice -- Sabrina and Evan -- Chapter 40 Fundamental Tax Law -- Connection Diagram -- Introduction -- Learning Objectives -- In Class -- Professional Practice Capabilities -- In Practice -- John and Susan -- Jose and Alexandra -- Gloria.
Includes index.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Financial planners; Investment advisors; Finance, Personal; Financial planning industry; Electronic books